FROM THE SCHOOL ENVIRONMENT TO THE HEALTH UNIT:: MENTAL HEALTH CARE FOR ADOLESCENTS (PRÁXIS EM SAÚDE, 2025)
This paper reports a psychological intervention experience with adolescents exhibiting anxiety symptoms, using mindfulness techniques from Dialectical Behavior Therapy (DBT), integrated with primary health care and the school context. The study was conducted with eight adolescents individually attended in basic health units (UBS), referred by public schools. The Hamilton Anxiety Scale (HAM-A) was used before and after a five-week protocol based on Marsha M. Linehan’s manual. Results showed an average reduction of 40% in psychic anxiety scores. Participants reported improvements in school concentration, calmness during assessments, and greater emotional autonomy. The experience highlights the potential of brief, evidence-based interventions to strengthen the connection between schools and UBS.
Keywords: Mental Health; Adolescence; Brief Psychotherapy; Mindfulness; Unified Health System